The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1516-35982012000900017
|View full text |Cite
|
Sign up to set email alerts
|

Economic viability of feeding dairy cows on diets containing different levels of soybean oil

Abstract: -The objective of this study was to evaluate the economic viability of feeding dairy cows with diets containing different levels of soybean oil. Cows were fed diets based on tropical forage (Pennisetum purpureum Schum) supplemented with different levels of soybean oil (0.0, 1.5, 3.0, and 4.5% of diet DM). The calculations were made considering the prices of the dietary ingredients and the daily consumption of each dietary treatment. The milk quality-based payment was estimated on the bonus paid for milk fat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…This fact highlights the economic unfeasibility of adding SFO to the experimental diets (Table 6). Similar results have been obtained by Lopes et al (2012), who analyzed the economic feasibility of adding soybean oil to elephant grass-based diets, and Lopes et al (2014), who evaluated SFO supplementation in sugarcane-based diets of lactating cows.…”
Section: Itemsupporting
confidence: 79%
See 1 more Smart Citation
“…This fact highlights the economic unfeasibility of adding SFO to the experimental diets (Table 6). Similar results have been obtained by Lopes et al (2012), who analyzed the economic feasibility of adding soybean oil to elephant grass-based diets, and Lopes et al (2014), who evaluated SFO supplementation in sugarcane-based diets of lactating cows.…”
Section: Itemsupporting
confidence: 79%
“…These findings suggest the importance of formulating low-cost diets, and the need to manipulate certain milk components. Lopes et al (2012) suggested that in addition to the payment policies presently adopted by several dairy companies in relation to somatic cell and total bacterial counts and protein and fat contents, bonuses should also be paid to farmers as an incentive to produce milk with nutraceutical potential that would benefit the health of consumers.…”
Section: Itemmentioning
confidence: 99%
“…The economic evaluation was calculated by the methodology of Economic Benefit, proposed by Lopes et al (2012), and also used by Lopes et al (2014) and Lage et al (2016). Estimated by the difference between the revenue obtained from the arrobas (@) produced in the period and leasing expenses of pasture (R$25,00/animal/month), consumption of mineral supplements and work labour used in supply.…”
Section: Methodsmentioning
confidence: 99%